automated analytical methodologies for determining flotation collectors "XANTHATES" and byproducts - Hidalgo Falla, P. (1998)
The present work was centred on the study of potassium ethylxanthate, EtX-K+, which displays a remarkable selectivity and is widely employed in the treatment of sulphide ore. It was synthesised in our laboratory and its characterisation was performed, alongside with purity assessment, by analytical assays (IR,UV) as well as by decomposition studies. In particular, we aimed to develop the polarography procedure: DC(tast) method coupled with a modern dropping mercury electrode. (SMDE) for the determination of EtX-K+, enabled us to obtain defined and reproducible anodic waves. The investigation was carried out in the presence of NaOH as a supporting electrolyte at pH 12.6 within a broad concentration range (2x10^(-6)-1x10^(-4) M). In a following stage, a flow injection analysis (FIA) system with amperometric detection with wall-jet type cells operated at -0.1 V fixed-potential was implemented. Fia-grams with reasonably reproducible peaks were generated, with a sample throughput capacity of 72 determinations/hour and detection limit is estimate in 0.16 ppm.